Pengaruh Model Pembelajaran Reciprocal Teaching terhadap Kemampuan Membaca Pemahaman Teks Berita Siswa Kelas VII SMP Negeri 2 Hiliduho - Julita Hertawati Lase; Noveri Amal Jaya Harefa; Mastawati Ndruru; Lestari Waruwu (Pusat riset dan Inovasi Nasional, 2025)
This study aims to determine the effect of the Reciprocal Teaching learning model on the reading comprehension ability of news texts among seventh-grade students at SMP Negeri 2 Hiliduho. The research employed a quasi-experimental method with a Nonequivalent Control Group Design. The pretest results showed that the initial abilities of students in the experimental and control classes were comparable, with average scores of 64.57 and 65.87, respectively. After the treatment, the experimental class showed a significant increase, achieving a posttest average of 81.52, while the control class only reached 74.35. The Reciprocal Teaching model proved effective in creating a collaborative learning environment, encouraging students to think critically, engage in discussions, and teach one another. In contrast, the control class, which used the Problem-Based Learning (PBL) model, demonstrated lower participation and higher dependence on the teacher. The hypothesis test showed a significance value of 0.001 < 0.05, indicating that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. These results indicate a significant effect of the Reciprocal Teaching model on students’ ability to comprehend news texts. Therefore, this model is recommended as an effective teaching strategy to enhance students’ reading comprehension, particularly in news text material at the junior high school level.